Antibiotic and Gene Profiles of Enterobacteriaceae from Selected Fish Ponds in Southwest, Nigeria - Joshua Ayedun; Cajethan Ezeamagu; Toyosi Osisami; Lawrence S. Owolabi (Fountain Journal of Natural and Applied Sciences (FUJNAS), 2022)
Fish is a significant part of human diet globally including Nigeria because of its economic and nutritional value. However, fish-associated infections caused by Gram negative bacteria of Enterobacteriaceae family have become a serious challenge with significant mortality in both aquaculture and healthcare institutions. With the increasing burden of antibiotics resistance in in this group of bacteria globally, the investigation of its resistance determinants and antibiotic profile was undertaken. A total of 64 fish pond water samples were collected from Lagos (16), Ogun (16), Oyo (16) and Osun (16). Enterobacteria were isolated by standard microbiological procedures and identified by 16S rRNA partial sequencing, after which antibiotic susceptibility test was performed using the Kirby-Bauer disc diffusion method. Resistance determinants were assayed by multiplex polymerase chain reaction. The family Enterobacteriaceae obtained were Enterobacter kobei (7), Enterobacter mori (9), Enterobacter asburiae (2), Enterobacter tabaci (2), Enterobacter sp. (27), and Plesiomonas shigelloides (5). Antibiotic susceptibility patterns revealed that all the (50) 100% isolates were resistant to ceftazidime, cefuroxime, cefixime and amoxicillin/clavulanic acid, while 28 (56%), 27 (54%) 17 (34%) and 15 (30%) were resistant to ciprofloxacin, nitrofurantoin, gentamicin and ofloxacin respectively. The resistance determinants; SHV (14), the integrons class 1 (14), QNRA (10), QNRS (9), TETB (9), QNRB (8) and TETA (7) were detected. The results revealed multidrug resistance among the isolates. This poses a serious health challenge to the consumers of fish. Therefore, proper monitoring of pond management system is important to prevent infections caused by these opportunistic pathogens.